ANALISIS KLUSTER UNTUK PEMETAAN MUTU PENDIDIKAN DI ACEH - , FADHLI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Cluster analysis is a multivariate technique that purpose for grouping object (or items) based on their characteristics. The object in a cluster has homogeny characteristic than the other cluster. The main steps in cluster analysis is to obtain clustering methods and distance measures. The problems examined in this study is how to classify the regencies in Aceh based on the National Examinationâs result at junior high school in 2010 used Mahalanobis distance to measure similarity and hierarchical clustering use average linkage. The results of data processing using Matlab showed that based on the results of National Examination at the junior high school in 2010, the regencies can be classified into two groups. The first group consist of twenty regencies with good quality in education and a second group consist of three regencies that are still lack in education quality.